Atrial fibrillation: Current knowledge and future directions in epidemiology and genomics - Magnani, Jared W. (2011)
Atrial fibrillation (AF) is of public health importance and profoundly increases morbidity, mortality and health-related expenditures. Morbidities include the increased risks of cardiovascular outcomes such as heart failure and stroke, and the deleterious effects on quality of life, functional status and cognition. The clinical epidemiology of AF, its risk factors and outcomes, have been extensively investigated. Genetic advances over the last decade have facilitated the identification of mutations and common polymorphisms associated with AF. Metabolomics, proteomics and other “omics” technologies have only recently been applied to the study of AF, and have not yet been systematically investigated. Systems biology approaches, while still in their infancy, offer the promise of providing novel insights into pathways influencing AF risk. In the present review, we address the current state of the epidemiology and genomics of AF. We seek to emphasize how epidemiology and “omic” advances will contribute towards a systems biology approach that will help to unravel the pathogenesis, risk stratification, and novel targets for AF therapies. Our purpose is to articulate questions and challenges that hinge on integrating novel scientific advances in the epidemiology and genomics of AF. As a reference we have provided a glossary in the inset box.